If it's not what You are looking for type in the equation solver your own equation and let us solve it.
28(5x+5)=82(2x+8)
We move all terms to the left:
28(5x+5)-(82(2x+8))=0
We multiply parentheses
140x-(82(2x+8))+140=0
We calculate terms in parentheses: -(82(2x+8)), so:We get rid of parentheses
82(2x+8)
We multiply parentheses
164x+656
Back to the equation:
-(164x+656)
140x-164x-656+140=0
We add all the numbers together, and all the variables
-24x-516=0
We move all terms containing x to the left, all other terms to the right
-24x=516
x=516/-24
x=-21+1/2
| 2z–15=30 | | x+2x+x+15+x+15-27=360 | | 5x=327 | | 28(2x+8)=82(5x-4) | | X+5x+28=70 | | 4t-3=5(t=4) | | 6x=27−3x | | 4x+5x-27=54 | | 11/12-1/6q+5/6=1/3 | | N/3+n/5=40 | | -3-b=-9 | | 6x+4x=330 | | 5x+3=-4x-6 | | 4(3j+(-4))=-9 | | (Y+3)+y=25 | | 4k=33 | | -10+x/4=-14 | | -3-b=9 | | 11z=50 | | 14d=33 | | -9+k/5=-5 | | (18+2x)-3=45 | | -8-2b=30 | | -2b+3=-21 | | 6a+12=4a+7 | | -7-10x=-197 | | -3.9(0.4x)2-3=0.1(x-5)2-3.2 | | (18+x)-3=45 | | 9r-9=153 | | 10+5x=-4 | | -2+2=2(x-4) | | 97=4(8.75x-2) |